Timber terminal capacity planning through queuing theory - Munisamy, S. (Palgrave Macmillan Ltd, 2010)
This article develops a port planning and operations model for capacity planning at a timber terminal. The analytical model underlying the system is the closed queuing network model. The model evaluates the efficiency of the timber terminal in relation to the cargo handling system and its impact on terminal throughput capacity. The model considers the interaction between cargo handling elements of a timber terminal, that is forklifts, tractors, trailers and quay cranes, to investigate congestion points and how each element affects the other parts of the cargo handling system. The output of the model is the performance statistics of the cargo handling equipments of the terminal, the throughput of quay cranes and the forecast of the terminal's throughput capacity. The implementation of the model to Port Klang timber terminal shows how it can provide guidance for port authorities and port operators in formulating economically efficient operational and expansion strategies.